Teacher’s management skills, well-being, religiosity, and academic motivation in Islamic education - Muhammad Thoyib; Subandi Subandi; Mispani Mispani; Aprezo Pardodi Maba; Suhono Suhono; Marlenatul Fitria (Institute of Advanced Engineering and Science, 2024)
Research on student academic motivation in Islamic educational institutions is currently in need of attention, as there are many schools based on Islam that have been overlooked by researchers. This research aims to investigate the role of perceived teacher management skills, psychological well-being, and religiosity towards students’ academic motivation using data from Muslim participants. A cross-sectional design was used to achieve the research objectives. A total of 318 participants (Female=200, Male=118, age M=16.7, age SD=1.9) were voluntarily involved in this research. Participants were asked for their willingness to fill out five scales. The collected data was then analyzed using descriptive analysis and multiple linear regression after the required conditions were met. The results of the research indicate that academic motivation is well predicted by perceived teacher management skills and psychological well-being. These findings highlight the importance of teachers showing mastery of management skills, including skills in maintaining interpersonal relationships with students and parents, and designing programs that can foster the psychological well-being of students.